Profile of Senior High School Metacognitive Ability in Solving Problems of Abstraction on Physics Material - Yanti, Helda; Distrik, I Wayan; Khasyyatillah, Isra (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2017)
This study aims to determine the ability of students’ metacognition in solving abstract problems in physical material. The study involved students who took through the test. Metacognition ability data obtained through written test consisting of questions metacognitive knowledge and metacognition skills. Data analysis is done descriptively. The result of the research shows that declarative knowledge dominates students metacognition knowledge, that is students can recognize the difficult problem and able to interpret in other forms but less able to recognize method used and how to finish, while students' metacognition skills are more dominant in planning and monitoring fields. Prediction and evaluation skills are still relatively low. Overall, metacognition ability of students included in the low category.